Transmedia Storytelling and Construction of Fictional Worlds: Aliados Series as Case Study - Atarama-Rojas, Tomás (2019)
This paper explores the contributions of transmedia storytelling in the construction of fictional worlds, in an attempt to detect the narrative elements that strengthen the bond of the audience with the fictional world. The study shows that based on the solid construction of the poetics of a story, transmedia storytelling can enrich the engagement with a large audience. To prove this, we analyze the narrative elements and the transmedia strategies of the series Aliados, produced by Cris Morena Group and broadcasted in Latin America and countries in Europe